KAJIAN PENGARUH KUASA KEPEMIMPINAN, MODEL MENTAL DAN EFEKTIVITAS TIM KERJA TERHADAP KOMITMEN KEPADA ORGANISASI - Setiadi, Iwan Kresna (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
The objectives of this research are to study the effects of supervisors’ effectiveness in using leadership power, supervisor’s mental model and team effectiveness on labours’ commitment to organization. The research was conducted in 2011 involving 250 labours of PT.KGM who were selected as respondents using simple random approach. The result of this research indicated the direct effects of: (1) supervisors’ effectiveness in using leadership power toward labour’s commitment to organization; (2) supervisors’ mental model toward labours’ commitment to organization and (3) team effectiveness toward labours’ commitment to organization. The result of this research also showed the indirect effects of: (1) the supervisor’s effectiveness in using leadership power toward labour’s commitment to organization through the team effectiveness; (2) supervisors’ mental model toward labour commitment to organization through the team effectiveness; This research conducted that labour’s commitment toorganization positively influenced by the supervisors’ effectiveness in using leadership power, supervisor’s mental model and team effectiveness.